A novel way of identification of recurrent laryngeal nerve during thyroid surgeries - Mathew, Joe (International Surgery Journal, 2021)
Background: This was a report of a movement of the recurrent laryngeal nerve which can be demonstrated during thyroid surgeries which can be used for locating the nerve, or identifying it if already exposed and causing confusion with other nearby structures or when alone too. Methods: The nerve is located by observing for a superior-inferior movement of the recurrent laryngeal nerve transmitted by the loose areolar tissue over it and dissecting over this site to locate the nerve right underneath it. This was by direct observation of the movement which will be there so long as the thyroid is held retracted to the opposite side and is not separated from the thyroid at the tissues that constitute the condensation of pre-tracheal fascia called the Berry’s ligament. Results: The recurrent laryngeal nerve originates from the vagus and loops posteriorly and then upwards around the arch of aorta on the left side and the subclavian artery on the right side. When the thyroid gland is retracted away and thus the nerve put on slight stretch, a superior-inferior to and fro- movement of the nerve can be seen. This movement can be used for identification and dissection of the nerve along its course. Conclusions: A review of literature has been done and it is clear that this movement has not been hitherto identified or published